The Effect of Time on Blood Types of ABO Systems on Saliva Spots of Cigarette Butts for Forensic Identification - Purnadianti, Mely; MAR, Mieke Sylvia; Yudianto, Ahmad (Folia Medica Indonesiana, 2018)
The identification process is not only carried out on the body of a victim of a crime, but identification can also be carried out on the evidence evidence found at the crime scene. The timing of a crime case and the time interval for collecting evidence of a crime is an obstacle in the process of identifying blood saliva on cigarette butts. Saliva will dry within an hour and forty minutes at room temperature and with the influence of various other factors saliva will dry in less than three hours. The purpose of this study was to determine the effect of the duration of temperature exposure on the protein levels of cigarette saliva in order to help the identification process of forensic blood groups. The time series design was used in this study where 18 filter cigarette butts were collected from 6 individuals who were subjected to research with blood types A, B and AB then incubated 1.3 and 6 hours. Examination of protein content was carried out using trizol reagent with UV spectrophotometer reading. The data was processed using non-parametric T-test statistics. There was a decrease in salivary levels in a predetermined time of 1, 3 and 6 hours. Cigarette butt saliva protein levels can still be detected within 1, 3 and 6 hours so that they can be used to help identify the forensic blood group from cigarette butt saliva.